Versailles: The phenomenology of architectural form - Dymchenko, Marina (project baikal, 2023)
The article identifies and describes the evolution of the architectural form of the Versailles Palace and Park Ensemble as a single spatial artistic experience. The change in the layout and structure of the palace is considered from the point of view of the general trend of Western European architecture – the appearance and development of Rococo in the bosom of architectonics and composition created in the Baroque manner, which evolved from classical Baroque in the Italian style to the purely national tradition of Rococo and early classicism. This forms a unique semantic space of the subject’s experience. The author formulates conceptual understanding of the change in the content of architectural form-making as a process of the constitution of the unique spatial structure of the “court” type of society, socio-cultural ties and relations and its gradual evolution from the Baroque mythologized theatricality of absolutism to the private type of structuration of the dwelling of the pre-revolutionary decades.
Keywords: Versailles; architectural form; phenomenology; space; construction; experience of subjectivity; baroque; rococo; art synthesis